Nordic nationalism and penal order: walling the welfare state - Barker, Vanessa (Routledge studies in criminal justice, borders and citizenship, 2018)
Nordic nationalism and penal order : puzzle, arguments and objectives -- The internal logic of the welfare state -- Mapping membership : social fault lines in Sweden -- Penal nationalism : its forms and functions -- Contesting the pain of others -- At the border fence : inward security, outward harm -- Appendix: research process and moments of discovery